Influence of HLA-B27 on the Phenotype and Severity of Spondyloarthritis: A Study from a Tertiary Care Center in Nepal - Khatri, Prabin; Shukla, Ravi; Adhikari, Raj; Shrestha, Puja; Parajuli, Rupesh; Subedi, Aabishkar (Journal of Manmohan Memorial Institute of Health Sciences, 2026)
Introduction: Spondyloarthritis is a group of chronic inflammatory disorders characterized by shared clinical and genetic features, commonly involving the axial skeleton and strongly associated with HLA-B27. However, the clinical profile and disease severity of HLA-B27-negative axial spondyloarthritis remains poorly defined, particularly in South Asian populations. This study aimed to evaluate the association between HLA-B27 status and clinical phenotype, disease activity, functional status, inflammatory markers, and radiographic severity in Nepalese patients Method: We conducted a cross-sectional study of adults with spondyloarthritis classified according to the ASAS 2009 criteria at a tertiary referral center in Kathmandu between October 16, 2025 to April 15, 2026. Clinical features, laboratory parameters, disease activity indices, and radiographic findings were compared between HLA-B27-positive and HLA-B27-negative groups. Multivariate logistic regression was performed to identify independent associations. Result: Out of 193 screened patients, 166 were included. The majority were male (80.3%), with a median age of 34 years. HLA-B27 was positive in 83.7% of patients. HLA-B27-negative patients presented at an older age (41 vs. 34 years) and had later symptom onset (32 vs. 25 years) compared to HLA-B27-positive patients. Family history was more common in HLA-B27-positive patients (32.4%, p=0.06). Dactylitis was significantly more frequent in HLA-B27-negative patients (33.3% vs. 8%, p=0.001) and remained independently associated (adjusted OR 6.25, 95% CI 1.9–20, p=0.002). No significant differences were observed in disease activity, inflammatory markers, or radiographic findings. Conclusion: HLA-B27 positivity was associated with earlier disease onset, whereas HLA-B27-negative patients exhibited more peripheral features, particularly dactylitis, with similar overall disease severity. Further longitudinal studies are needed to validate these findings.